2017
DOI: 10.1523/jneurosci.1188-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Laterality in Forelimb-Movement Representations of Rat Primary and Secondary Motor Cortical Neurons with Intratelencephalic and Pyramidal Tract Projections

Abstract: Two distinct motor areas, the primary and secondary motor cortices (M1 and M2), play crucial roles in voluntary movement in rodents. The aim of this study was to characterize the laterality in motor cortical representations of right and left forelimb movements. To achieve this goal, we developed a novel behavioral task, the Right-Left Pedal task, in which a head-restrained male rat manipulates a right or left pedal with the corresponding forelimb. This task enabled us to monitor independent movements of both f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
73
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 67 publications
17
73
1
Order By: Relevance
“…To this end, we divided continuous paw movements during ex-ploratory behavior into artificial trials by setting a threshold of the paw speed (for details see methods 6.3.4). In line with previous work based on instructed tasks [15], neurons in motor cortex were modulated by the movements of the contralateral but not the ipsilateral paw in a ± 333 ms window around movement onset ( Fig. 4a,b, two-sided t-test on mean normalized firing rate across population, p< 0.05).…”
Section: Neuronal Representations Of Behavioral States and Paw Trajecsupporting
confidence: 91%
“…To this end, we divided continuous paw movements during ex-ploratory behavior into artificial trials by setting a threshold of the paw speed (for details see methods 6.3.4). In line with previous work based on instructed tasks [15], neurons in motor cortex were modulated by the movements of the contralateral but not the ipsilateral paw in a ± 333 ms window around movement onset ( Fig. 4a,b, two-sided t-test on mean normalized firing rate across population, p< 0.05).…”
Section: Neuronal Representations Of Behavioral States and Paw Trajecsupporting
confidence: 91%
“…This idea of lateralization of function in the rodent brain has been a topic of longstanding yet of sporadic interest in the field (Glick and Ross, 1981;Kim et al, 2012;Soma et al, 2017;Wu et al, 2014). However, the underlying cellular mechanisms governing laterality are unknown.…”
Section: What Governs Pnn Dynamics In Adults?mentioning
confidence: 99%
“…Neuroimaging and electrophysiological studies in humans and monkeys have shown that unilateral movements are associated with preferred activation (lateralization) of the contralateral primary motor cortex (M1), premotor cortex (PM) and supplementary motor area (SMA; Colebatch et al, 1991; Catalan et al, 1998; Mattay et al, 1998; Solodkin et al, 2001; Kurata, 2007). However, there is a difference in the degree of lateralization among M1 and other motor areas: the preferred activation during contralateral movements in M1 contrasts with the bilateral activation of PM (Kurata, 2007; Soma et al, 2017, 2019). Imaging studies have revealed that the lateralization in the motor cortex is diminished in PD (Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 98%